2018
DOI: 10.1136/annrheumdis-2017-212454
|View full text |Cite
|
Sign up to set email alerts
|

Changes in macrophage transcriptome associate with systemic sclerosis and mediate GSDMA contribution to disease risk

Abstract: ObjectivesSeveral common and rare risk variants have been reported for systemic sclerosis (SSc), but the effector cell(s) mediating the function of these genetic variants remains to be elucidated. While innate immune cells have been proposed as the critical targets to interfere with the disease process underlying SSc, no studies have comprehensively established their effector role. Here we investigated the contribution of monocyte-derived macrophages (MDMs) in mediating genetic susceptibility to SSc.MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 32 publications
2
51
2
Order By: Relevance
“…65 Although GRB10’ s role in immunity is still unclear, it has been associated with a subtype of systemic sclerosis (lcSSc); patients with systemic sclerosis have higher expression of GRB10 in monocytes. 66,67 Studies of Grb10 deficient mice demonstrated Grb10 ’s role in hematopoietic regeneration in vivo . 68 Additionally, in a transcriptome study of CD4+ Effector Memory T cells (CD4 + T EM ), GRB10 was the most significantly downregulated gene after T-cell receptor stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…65 Although GRB10’ s role in immunity is still unclear, it has been associated with a subtype of systemic sclerosis (lcSSc); patients with systemic sclerosis have higher expression of GRB10 in monocytes. 66,67 Studies of Grb10 deficient mice demonstrated Grb10 ’s role in hematopoietic regeneration in vivo . 68 Additionally, in a transcriptome study of CD4+ Effector Memory T cells (CD4 + T EM ), GRB10 was the most significantly downregulated gene after T-cell receptor stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, several papers showed that a main mechanism of action of MSCs from adipose tissue, is to promote tissue regeneration through M2 polarization [38][39][40], but hypoxia reduces their capability to polarize macrophages in the M2 phenotype [41] while for the PB-MNCs hypoxia is a physiological trigger for angiogenesis [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by controlling the family-wise error rate (FWER: probability of at least one false positive) using the Bonferroni method [65]: = 0.05 / number of genes to guarantee FWER < 0.05. To obtain a range of typical effect sizes and mean expression distributions in specific immune cell types, we analysed several DEG studies based on FACS sorted bulk RNA-seq [54,55]. Combining our model for gene expression in scRNA-seq experiments with this power analysis of DE genes, we can calculate the overall detection power of DE genes in a scRNA-seq experiment as the product of the expression probability of the gene and the DE power for the gene (see Formula 1).…”
Section: Expression Probabilitymentioning
confidence: 99%
“…When published, we took directly the effect sizes, otherwise we recalculated the DE analysis with DEseq2. Differential gene expression: To get realistic estimates for effect sizes (fold changes), data sets from FACS sorted bulk RNA-seq studies were taken [54,55]. The data sets were used to rank the expression level of the DEGs among all other genes using the FPKM values.…”
Section: Pilot Data Setsmentioning
confidence: 99%
See 1 more Smart Citation